PENERAPAN REWARD AND PUNISHMENT DALAM MENINGKATKAN KEDISIPLINAN DAN HASIL BELAJAR SISWA PADA KEGIATAN PEMBELAJARAN TEMATIK KELAS II MIN 1 SABANG - Anisatul Ulfa; Daniah; Irwandi (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Discipline is one of the factors that can affect the improvement of learning outcomes. However, there are still many students who are not aware of the importance of discipline in the learning process such as students not doing assignments or copying friends' assignments, this results in many students whose grades do not reach the Minimum Completeness Criteria (KKM). One of the strategies implemented to improve discipline and learning outcomes is by giving reward and punishment. The aims of this study were: (1) to find out the activities of teachers and students after applying reward and punishment in class II/b, (2) to find out the level of discipline and student learning outcomes after implementing reward and punishment in class II/b. This type of research is Classroom Action Research (PTK) which is carried out in 4 stages, namely planning, action, observation, and reflection. The research instrument was in the form of teacher activity observation sheets, student activity observation sheets, disciplinary observation sheets, and student learning outcomes test sheets. The results showed that (1) the percentage of teacher activity research results in cycle I was 77.77% in the good category and increased in cycle II to 89% in the excellent category, (2) the percentage of student activity research results in cycle I was 78 .85% in the good category and in cycle II it becomes 89% in the very good category, (3) the percentage of student discipline in cycle I is 76% in the good category and in cycle II it becomes 80% in the good category, (4) the percentage of learning outcomes students in cycle I, namely 62% in the good category and experienced an increase in cycle II to 92% in the very good category. Based on the results of these data it can be concluded that the application of reward and punishment can improve discipline and student learning outcomes in thematic learning activities for class II students MIN 1 Sabang.